Justification Of Thrust Bearings Parameters For Increasing The Reliability Of Downhole Pumps - Pulatov T.R., Asanov S., Hoshimov A.A (International Journal of Advanced Science and Technology, 2020)
This article provides a study of factors affecting the reliability and durability of thrust bearings inelectric centrifugal pumps of the ECW type. For these factors, a number of analytical equations arepresented that can be used in determining the parameters for friction pairs of thrust bearings ofturbine generators of hydroelectric stations. The methodology for testing to determine the operationalroughness of friction pairs established after the end of the running-in process is described in detail.During of the experiments, values of roughness parameters differing from the initial values wereobtained. The initial production of surfaces of friction pairs with parameters closer to operationalgives a faster transition to equilibrium roughness, a decrease in initial wear and an increase in thereliability of friction pairs. It is recommended to produce sliding friction pairs of downhole pumpswith roughness parameters Ra=0.31-0.37 μm.